Using a solar photovoltaic-thermal system, and a new hydrogen liquefaction system based on the enhanced claud cycle, design and multi-objective optimization. (March 2023) - Sharifi, Ali; Jafari, Moharram; Ranjbar, Faramarz; Talati, Faramarz
Abstract: According to research by the International Energy Agency, fossil fuels have met around 80% of the world's energy demands in recent years, which has increased CO2 emissions, which primarily function as greenhouse gases. The transition to more efficient energy systems that employ renewable energy sources, among other things, in order to reduce environmental issues and reduce our reliance on fossil fuels, is inevitable. Hydrogen fuels are reliable and available renewable resources since they are affordable and have the potential to produce net zero carbon emissions. This study will demonstrate a technique for using solar energy to generate electricity and liquid hydrogen. The benefits of the proposed system will be examined in comparison to both standard liquefaction systems and the fundamental systems that power and cool them. The fundamental variables that determine more effectiveness, cheaper cost, more liquid hydrogen generation, and less pollution will be examined, and then optimization to accomplish all of the objective functions at once will be covered. The findings indicate that the actual work consumption in the liquefaction cycle is calculated to be 54301 kJ/kg H2. Also, as solar panel size grows, the volume of liquid hydrogen increases by 37.5%, and the highest surface of the panels provides the maximum power, or 4550 kW. Additionally, the system has a 56.3% efficiency, 13 kg/s of liquid hydrogen, and a cost 15.1 /GJ.